2003
DOI: 10.1039/b212535h
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of TiO2 thin films on polystyrene by liquid phase deposition

Abstract: Polystyrene (PS) substrates were functionalized by wet chemical grafting with 2-acrylamido-2-methylpropane-1sulfonic acid (AMPS). Subsequently, TiO 2 thin films were prepared by liquid phase deposition (LPD) with an average growth rate of 85 nm h 21 ; a maximum thickness of 750 nm was observed in our experiments. The crystalline fraction of the precipitated material was estimated to be 58% by X-ray powder-diffraction. Significantly improved film adhesion was achieved on grafted substrates, as compared to non-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
43
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(47 citation statements)
references
References 20 publications
(24 reference statements)
4
43
0
Order By: Relevance
“…An understanding of the deposition mechanism on self-assembled monolayers has been described [7] .Recently, it has been shown that planar polystyrene substrates [8] and even polymer microcapsules [9] can be coated by LPD. These results indicate that LPD should be a viable method for TiO 2 thin fi lms formation on the curved surface of fi brous materials.…”
Section: Introductionmentioning
confidence: 98%
“…An understanding of the deposition mechanism on self-assembled monolayers has been described [7] .Recently, it has been shown that planar polystyrene substrates [8] and even polymer microcapsules [9] can be coated by LPD. These results indicate that LPD should be a viable method for TiO 2 thin fi lms formation on the curved surface of fi brous materials.…”
Section: Introductionmentioning
confidence: 98%
“…There has been some work reported on the use of surface modified polymers such as sulfonated polystyrene as substrates for ceramics such as (0 0 l) oriented calcium carbonate (Addadi et al, 1987), (0 2 0) oriented goethite ( -FeOOH) or titanium dioxide (Dutschke et al, 2003). In a previous preliminary communication, we have shown that oriented dense thin films of Mg 2+ /Al 3+ -carbonate LDHs (Mg 4 Al 2 (OH) 12 (CO 3 ) · 4H 2 O, MgAl-LDH) may be grown on sulfonated polystyrene substrates with the (0 0 l) planes of the LDH platelets perpendicular to the surface of the substrates (Lei et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…These can react with the silanes and form a SAM, which is basic for patterning using the method for ceramics. Recent progress in this area involves preparation of an intermediate active layer, a silica-like layer as thin as molecular scale on the surface of polymers, by either chemical grafting [229][230][231][232][233][234][235] or physical deposition.…”
Section: Examples Of Iron Oxidesmentioning
confidence: 99%
“…Typically, these problems are overcome by increasing the surface energy of the materials through introducing polar functionality by either physical (X-ray, laser, ion beam, plasma treatment, or flame treatment) [218][219][220][221][222][223][224][225][226][227][228] or chemical surface modification. [229][230][231][232][233][234][235] Plasma treatment using different gases produces different reactive radicals. Oxygen creates hydroxy, carbonyl, carboxyl, ester, ether, and hydroperoxyl functional groups, among others.…”
Section: Examples Of Iron Oxidesmentioning
confidence: 99%